2018
DOI: 10.1377/hlthaff.2018.0720
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of A Communication-And-Resolution Program On Hospitals’ Malpractice Claims And Costs

Abstract: To promote communication with patients after medical injuries and improve patient safety, numerous hospitals have implemented communication-and-resolution programs (CRPs). Through these programs, hospitals communicate transparently with patients after adverse events; investigate what happened and offer an explanation; and, when warranted, apologize, take responsibility, and proactively offer compensation. Despite growing consensus that CRPs are the right thing to do, concerns over liability risks remain. We ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Although there may be legal risks to the institution, disclosing potential outbreaks may increase public perception of the hospital’s integrity and reduce the chance that the public will view the hospital as having withheld information from patients. One recent study at four Massachusetts hospitals found that malpractice claims did not increase following implementation of a communication-and-resolution program through which the hospitals communicated with patients about adverse events and took responsibility when appropriate [35]. Hospitals should consult their legal counsel, communications experts, and state public health department for additional assistance.…”
Section: Components Of An Outbreak Investigationmentioning
confidence: 99%
“…Although there may be legal risks to the institution, disclosing potential outbreaks may increase public perception of the hospital’s integrity and reduce the chance that the public will view the hospital as having withheld information from patients. One recent study at four Massachusetts hospitals found that malpractice claims did not increase following implementation of a communication-and-resolution program through which the hospitals communicated with patients about adverse events and took responsibility when appropriate [35]. Hospitals should consult their legal counsel, communications experts, and state public health department for additional assistance.…”
Section: Components Of An Outbreak Investigationmentioning
confidence: 99%
“…24,25 Aligning the principles of risk management ethics with those most often referenced by clinicians creates a shared ethical vocabulary and helps establish the legitimacy of the broader suite of principles among patients and other stakeholders. 26,27,28,29 Nonmaleficence The obligation to avoid actively causing harm ("first do no harm"), as opposed to the broader obligation to prevent harm from being caused Apart from disclosure/apology and compensation programs, 27,30,31 current literature provides scant support for assessing how risk management practice can inflict (or avoid inflicting) harm.…”
Section: Purposes Of Risk Managementmentioning
confidence: 99%
“…• Concerns about restorative justice underlie disclosure/apology and compensation programs. 27,30,31 Respect for Autonomy A duty to (1) refrain from attempting to control and constrain the autonomous actions of others and (2) actively support autonomous decision making, especially by disclosing relevant information.…”
Section: Justicementioning
confidence: 99%
“…shown that a prompt sincere apology and communication to investigate the case and develop future prevention from healthcare providers can reduce the situation's escalation to a lawsuit in several countries and settings [18][19][20]. Physicians who understand and can respond appropriately to the emotional needs of their patients are less likely to be sued [21].…”
Section: A Balance Of Monetary and Non-monetary Remedies For Victims mentioning
confidence: 99%